Interpretation of cultural heritage: approaches and methods of excursion work - Hutsal, Liudmyla (Journal of Education, Health and Sport, 2024)
The article deals with the problem of interpreting cultural heritage in the context of modern society, which faces numerous challenges, including globalisation, technological changes and the need to preserve cultural values. Cultural heritage, which encompasses both tangible and intangible elements, is an important aspect of a nation’s identity and history. However, in today’s environment, traditional approaches to sightseeing do not always meet the needs of the audience, particularly young people who seek interactive and emotionally charged experiences. The article offers an analysis of the main approaches to the interpretation of cultural heritage, including scientific, educational, aesthetic and socio-cultural. The scientific approach focuses on the objective study of heritage sites, while the educational approach involves engaging a wide audience through interactive elements and new technologies. The aesthetic approach focuses on the emotional perception of heritage, while the socio-cultural approach takes into account the context of cultural values and involves local communities in the process of their interpretation. The article also analyses the methods of excursion work, such as thematic and interactive excursions, excursions using new technologies, as well as specialised programmes for specialists. The latest research by Ukrainian scholars is considered, which emphasises the importance of innovative approaches in this area. Thus, the article concludes that an integrated approach to the interpretation of cultural heritage is needed to ensure its preservation and active use, as well as the formation of respect for cultural values in society. It is also important to involve local communities in the processes of preserving and promoting cultural heritage, which will increase their activity and awareness in this area.